Strong intra-species variability in the metabolic conversion of six procarcinogens to somatic cell recombinagens in Drosophila. - Rodriguez-Arnaiz, R.; Vogel, E.W.; Szakmary, A. (Mutagenesis, 1993)
Genetic heterogeneity in response to genotoxic carcinogens requiring metabolic conversion has been studied in Drosophila, using seven different genotypes in combination with the w/w+ eye mosaic assay for mitotic recombination. The set of tester strains examined consisted of four wild-type laboratory strains (Berlin-K, BK; Oregon-K, OK; Leiden-S, LS; and 91-C), and three DDT-resistant strains (91-R; Hikone-R, HR; and Haag-79, HG). Drosophila larvae heterozygous for the wild-type report gene w+ were exposed to benz[a]anthracene (BA), benzo[a]pyrene (BP), 9,10-dimethyl-anthracene (DA), monocrotaline (MC), N-nitrosodimethylamine (DMN) or vinyl bromide (VBr). The primary conclusion regarding this study is the up to 60-fold variation between different genotypes in mosaic spot frequencies induced by those procarcinogens and the non-existence of just one genotype to function as a 'super-strain' in the activation of different classes of procarcinogens. By contrast, the seven Drosophila strains show a similar response to the direct-acting agent methyl methanesulphonate. Among the six procarcinogens selected for this study, DMN and MC are readily detectable in all the distinct genotypes. Less satisfactory in terms of test performance are the either negative or weak test responses with BA in all four-wild type strains (LS, BK, OK and 91-C), and the weakly positive results for vinyl bromide in LS, BK and OK. The best overall test response was provided by strains HG and HR. It is concluded that the combined application of strains HG and HR safely and reliably should detect somatic cell recombinagens in the Drosophila w/w+ system.(ABSTRACT TRUNCATED AT 250 WORDS)